Rapid PCR based identification of two medically important dermatophyte fungi, Microsporum canis and Trichophyton tonsurans - Malinovschi, Gabriela (Acta Biologica Szegediensis, 2009)
PCR-based species specific protocols have been worked out for two important pathogens M. canis and T. tonsurans responsible for dermatophytosis with various clinical appearances. Reactions were designed to use a common reverse primer and 2 specific forward primers and were optimised to be efficient under the same PCR conditions allowing the detection of these two fungi from one reaction volume. The specific PCR reactions were evaluated both on collection strains of other dermatophytes and on clinical samples. In connection with these methods, different DNA extraction techniques were also tested to assist for an efficient PCR based detection.